Tradisi Pasambahan Basigorak dalam Adat Perkawinan di Kelurahan Padang Tangah Payobada Kecamatan Payakumbuh Timur: Analisis Struktur, Fungsi, dan Konteks - Edly, Sheffy; Juita, Novia; Tamsin, Andria Catri (Universitas Negeri Padang, 2012)
The purpose of this study is to describe and analysis the structure, function and context Pasambahan Basigorak in a wedding party in Padang Tangah Payobada, East part Of Payakumbuh district. The data is Pasambahan Basigorak in Padang Tangah. The source of this research is spoken source as the primary source that told by its original speaker. The data is collected using the recording, interview, and writing technique as exetended technique. The founding of the research consist of three founding, is (1) Pasambahan Basigorakâ€™s stuctureÂ consist of opening, body, and closing, (2) the function of Pasambahan Basigorak consist of social function, educational function, moral function, custom function, and language function, the last (3) the contexts are situation and culture contexts.